Artificial Intelligence for Academic Writing from Gen Z’s Perception: The Application, The Advantages, and The Challenges - Rosalina, Elsa; Umar, Vebrianti; Pitria Ningsih, Rahma; Asrimawati, Inayati Fitriyah; Hikmah, Hikmah (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
The increase of integration of Artificial Intelligence (AI) in academic writing has raised questions about its impact on the writing practices and perceptions of Generation Z (Gen Z) students. Although some AI technologies for academic writing nowadays have shown significant benefits, there is a lack of consensus among Gen Z students on how these tools support or hinder their academic writing processes. The research problem centers on understanding the varying perceptions of Gen Z students towards AI tools in academic writing and identifying factors that influence their adoption and usage of such technologies in academic context. This qualitative research is conducted to understand the subjective experiences and perceptions of Gen Z students through in-depth exploration and analysis. It involves the collection and analysis of non-numerical data to uncover insights into students' views on AI integration in academic writing. The research subjects were Generation Z students currently enrolled in higher education institutions. These students were selected based on their exposure to and usage of AI tools in academic writing, with a particular focus and those who are willing to be interviewed. The data were collected through semi-structured interviews and open-ended questionnaire. The data collected were then analyzed using Miles and Hubberman. The research results show that not all members of Gen Z share the same perceptions regarding the use of AI to support academic writing. However, most of them agree that AI has become an inseparable part of human life. As students, they recognize the need to adapt to these changes and keep pace with the  evolving era. They also acknowledge that it is impossible to overlook the transformations happening in the education sector